Sosialisasi Pentingnya Freight Forwarding Dalam Menunjang Efisiensi Logistik Global Pada Akmi Suaka Bahari Cirebon - Fajar, Fajar Transelasi; Wahyuni, Okvita; Prasetiawan, Andi (Politeknik Ilmu Pelayaran Semarang, 2025)
Freight forwarding plays a strategic role in supporting global logistics efficiency, particularly in addressing the challenges of cross-border goods distribution. This socialization activity aims to raise awareness among the academic community of AKMI Suaka Bahari Cirebon regarding the importance of freight forwarding in international logistics processes and its contribution to the smooth operation of global supply chains. The methods used included interactive counseling, material presentations, and group discussions involving students from relevant study programs. The results of the activity indicated an increased understanding among participants of the core functions of freight forwarders, such as handling export-import documentation, managing transportation modes, and optimizing both cost and time in goods distribution. This initiative is expected to enhance students’ logistics competencies and strengthen the synergy between educational institutions and the needs of the global logistics industry. Keywords: Freight Forwarding, Global Logistics, Efficiency, Socialization, AKMI Suaka Bahari Cirebon